One-Pot Conversion of Aldehydes and Ketones into 1-Substituted and 1,4-Disubstituted 1,3-Enynes - Cabezas Pizarro, Jorge A. (2018)
Sequential treatment of 2,3-dichloropropene with magnesium and n-BuLi generates the operational equivalent of 1,3-dilithiopropyne, which upon treatment with aldehydes or ketones, produces the corresponding alkoxy lithium acetylide intermediates. Reaction of this alkoxide with tosyl chloride, and t-BuLi produces 1-substituted, or 1,1-disubstituted 1,3-enynes in a one-pot reaction. When this lithium acetylide intermediates, obtained by this procedure, were used to perform palladium-catalyzed cross-coupling reactions, followed by addition of thionyl chloride and pyridine, 1,4-disubstituted or 1,1,4-trisubstituted 1,3-enynes were obtained in a one-pot protocol.